Resolving land and energy conflicts - Field, Patrick; Kansal, Tushar; Morris, Catherine; Smith, Stacie (Anthem ecosystem services and restoration., 2018)
Based on decades of experience in addressing energy-siting conflicts, the authors of 'Resolving Land and Energy Conflicts' provide details of a host of tools, strategies and principles for tackling them.